에마맥틴 벤조에이트(Emamectin Benzoate) 성분 농약에 노출된 넙치(Paralichthys olivaceus)의 폐사, 혈액학적 및 조직학적 영향 분석 - 이승준; 박보령; 이은섭; 김한을; 권준영; 권세련; Sung Jun Lee; Park Bo Ryung; Eunsup Lee; Han Eul Kim; Joon Yeong Kwon; Se Ryun Kwon (한국해양생명과학회지, 2025)
In this study, we investigated the mortality, hematological and histological changes in olive flounder (Paralichthys olivaceus) exposed to a pesticide with emamectin benzoate (EB) as the active ingredient, which poses a risk of coastal runoff. EPC cells were exposed to EB-containing pesticide at concentrations of 0.215, 2.15, 21.5, and 215 ppm for in a 96-well plate, 48 hours to assess cytotoxicity. Cell detachment was observed at concentrations of 21.5 ppm and 215 ppm, and the cell viability at 215 ppm was 4.12 ± 1.8%. The olive flounder was placed in a polypropylene tank (capacity 300L) were exposed to Pesticide with emamectin benzoate as the active ingredient for 48 hours, all died at concentrations of 2.15 ppm and 21.5 ppm, whereas no mortality was observed at concentrations of 0.0215 ppm and 0.215 ppm. Hematological analysis revealed that the plasma glucose concentration in fish exposed to 21.5 ppm was 1.52 times higher than that of the control, and the total protein concentration increased by 0.71-fold and 0.74-fold at 2.15 ppm and 21.5 ppm, respectively, compared to the control. Cholesterol and alkaline phosphatase levels increased by 2.84-fold, 2.44-fold, and 3.8-fold, respectively, at 21.5 ppm compared to the control. Aspartate aminotransferase and alanine aminotransferase levels increased by 0.4-fold and 0.5-fold, respectively, at 21.5 ppm compared to the control. These results indicate that concentrations of 21.5 ppm or higher induce acute mortality in olive flounder and cause Increased stress due to increased glucose levels and liver and kidney damage. Meanwhile, short-term exposure (48 hours) to EB-containing pesticide did not induce lesions in liver tissue. 본 연구에서는 연안으로 유출 위험이 있는 에마멕틴 벤조에이트(emamectin benzoate, EB) 성분의 농약에 대한 넙치의 폐사, 혈액학적 변화, 조직학적 변화를 확인하였다. EB 성분 농약을 96-well plate에서 48시간 동안 0.215, 2.15, 21.5, 215ppm의 농도로 EPC 세포에 노출한 후 세포 독성을 확인한 결과, 21.5ppm과 215ppm의 농도에서 세포 박리가 확인되었고 215ppm에서는 4.12±1.8%의 세포 생존율이 확인되었다. 넙치를 polypropylene수조(용량 300L)에 순치하고, EB 성분 농약을 침지법으로 48시간 동안 노출한 결과, 2.15ppm 21.5ppm 농도에서는 넙치가 모두 폐사했지만, 0.0215ppm과 0.215ppm 농도에서는 폐사가 관찰되지 않았다. 혈액학적 분석 결과, 혈장 glucose 농도는 21.5ppm 노출 넙치에서 control 대비 1.52배 증가하였고, total protein 농도는 2.15ppm, 21.5ppm 농도에서 control 대비 각각 0.71배, 0.74배 증가하였다. Cholesterol, alkaline phosphatase은 21.5ppm 농도에서 control 대비 각각 2.84배, 2.44배, 3.8배 증가하는 것을 확인하였다. Aspartate aminotransferase와 alanine aminotransferase는 21.5ppm 농도에서 control 대비 각각 0.4배 및 0.5배 증가하는 것을 확인하였다. 이상의 결과로, 21.5ppm 이상의 농도는 넙치의 급성 폐사를 유발하며, gluscos수치 증가로 인해 스트레스 증가 및 간과 신장 손상에 의한 혈액학적 변화를 유발하는 것을 확인할 수 있었다. 한편 EB 성분 농약을 48시간 동안 단기간 처리하는 것에 의해서는 간 조직에 병변을 유발하지는 않았다.